2016
DOI: 10.1155/2016/6760243
|View full text |Cite
|
Sign up to set email alerts
|

Deep Brain Stimulation Frequency of the Subthalamic Nucleus Affects Phonemic and Action Fluency in Parkinson’s Disease

Abstract: Introduction. Deep brain stimulation of the subthalamic nucleus (STN-DBS) in Parkinson's disease (PD) has been linked to a decline in verbal fluency. The decline can be attributed to surgical effects, but the relative contributions of the stimulation parameters are not well understood. This study aimed to investigate the impact of the frequency of STN-DBS on the performance of verbal fluency tasks in patients with PD. Methods. Twenty individuals with PD who received bilateral STN-DBS were evaluated. Their perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 37 publications
4
17
0
Order By: Relevance
“…Again, low frequency stimulation might be helpful in improving VF after STN-DBS [22,26] The main aim of this study was to examine how articulation, respiration, phonation, resonance, prosody and rate respond to LFS (60Hz, 80Hz) in comparison to 110Hz, 130Hz and 200Hz and how this contributes to overall speech intelligibility. A further aim was to establish the effect of LFS and HFS on PVF and SVF and whether cluster size and switching are altered by stimulation frequency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Again, low frequency stimulation might be helpful in improving VF after STN-DBS [22,26] The main aim of this study was to examine how articulation, respiration, phonation, resonance, prosody and rate respond to LFS (60Hz, 80Hz) in comparison to 110Hz, 130Hz and 200Hz and how this contributes to overall speech intelligibility. A further aim was to establish the effect of LFS and HFS on PVF and SVF and whether cluster size and switching are altered by stimulation frequency.…”
Section: Introductionmentioning
confidence: 99%
“…They attributed this to activation of neural pathways projecting to the inferior frontal cortex providing evidence of frequency dependent tuning of cognitive circuits interconnected with the STN, where DBS of the STN at 10 Hz might have an inhibitory effect on the motor circuit and yet a facilitatory effect on the cognitive circuit. Fagundes, et al[26] also found that, PVF, but not SVF responded favourably to LFS, proposing that due to frontocortical impairment in PD, a frequency effect would manifest to a greater extent in tasks that make demands on frontocortical functions such as PVF.…”
mentioning
confidence: 96%
“…Some 30 years ago, it was observed that high-frequency stimulation (∼130 Hz) in the basal ganglia relay nucleus, the subthalamic nucleus, had a remarkable effect of alleviating Parkinson's disease symptoms [50,54,57,78,80]. Clinically, the impact of DBS strongly depends on stimulation amplitude and frequency [81]: too-high stimulation frequencies (>180 Hz) were reported to be therapeutically ineffective [50,82], while too low stimulation frequencies have a still debated impact. Indeed, some studies showed that low-frequency stimulation could worsen some parkinsonian symptoms such as tremors and rigidity [83], possibly by imposing another oscillatory rhythm onto the basal ganglia network, while others showed a beneficial impact of lowfrequency stimulation for gait control and cognitive functions [84].…”
Section: Oscillations-induced Desynchronization and Parkinson's Dmentioning
confidence: 99%
“…There are some data that low-frequency (60 Hz) stimulation may prove less likely to alter verbal fluency and gait when compared to higher-frequency (130 Hz) stimulation. 17,40,60,61 The literature reveals variation in patient response, 40 potentially transient effectiveness, 51 and often decreased effectiveness in treating appendicular symptoms, tempering enthusiasm for application of low-frequency There is evidence that LFP signals in the STN can be used identify a variety of behaviors, including speech, motor, and random movement with up to 73.2% accuracy. 44 STN LFP features, such as synchronization and interhemispheric connectivity features based on wavelet transform and Granger causality approaches, have achieved an average accuracy of 99.8% for movement identification, and 81.5% for laterality classification.…”
Section: Other Approachesmentioning
confidence: 99%